Exploring CDKs, Ras-ERK, and PI3K-Akt in Abnormal Signaling and Cancer (Journal of Cancer Research Updates, 2022)
Cancer or malignancy can be defined as abnormal growth and cell division. Malignancies spread, through metastasis invasion, or implantation into distant sites by which cancer cells can move through the bloodstream or lymphatic system to distant locations. The body cells follow the mitotic cell division process. Normal cell division occurs through the normal signal transduction through proto-oncogenes responsible for cell proliferation and differentiation. Mutation of these proto-oncogene leads to oncogene which can modify the gene expression and function through abnormal signal transduction, making uncontrolled growth of cells. The mitotic cell cycle is regulated by signal transduction through the cyclin-dependent kinases (CDKs), Ras-ERK, and PI3K-Akt. Abnormal signaling occurs through the mutation of these genes leading to cancer. The present review shortly reported the role of these proteins in abnormal signal transduction and cancer.